Mechanism of Salt Stress Tolerance in Plants: Role of Cation/H+ Antiporters - Qurban Ali; Muzammal Mateen Azhar; Arif Malik; Shahbaz Ahmad; Muhammad Zafar Saleem; Muhammad Waseem (AGRIVITA, Journal of Agricultural Science, 2020)
Salinity is an important adverse environmental problem that caused a loss in the sense of reducing yield per plant, morphological, and physiological functions of crop plants. The plants compete with environmental stress conditions to withstand following normal growth and development. The exchange of cations or protons (H+) takes place across the cell membrane to maintain the osmotic pressure of cells under salt stress conditions. There is a huge number of cation/H+ antiporter 1 protein-producing gene by plant cells under salt stress conditions has been identified. However, a few have been characterized and sequenced which contributes to ion homeostasis and osmotic adjustment of cells. These cation/H+ antiporters are produced and stored in the vacuoles, endosomal forms and in the cytoplasm. The cation/H+ antiporters are involved in the homeostasis of K+, Na+, and pH of the cell under salinity stress conditions. The cation/H+ antiporters help plants cells to regulate all physiological functions under salt stress conditions.